As vozes sociais emergentes no conto Onde acaba o mapa, de Carol Rodrigues - Silva, Daiane Corrêa da (2018)
This work, called As vozes sociais emergentes no conto Onde acaba o mapa, written by Carol Rodrigues, has as a theme the emergency of social voices in the short story of Onde acaba o mapa. The general objective is to identify the emerging voices of the linguistic choices present in a short story of Carol Rodrigues‟s book Sem Vista para o mar (contos de fuga), and analyze the possible effects of meaning arising from these choices. A study of this nature is justified by noticing that the literary text is a privileged place to analyze the discourse and understand it as an ideological creation, product of the interaction between interlocutors inserted in a social environment. This work is based on the theoretical construction of the Bakhtin Circle and Bakhtin‟s socioenuciative perspective of language derived from the books Marxism and the Philosophy of language (2014), Aesthetics of Verbal Creation (2015a), Problems of Dostoevsky‟s poetics (2015b), Discourse in Life, Discourse in art (about sociological poetics) (1976) and Questions of Literature and Aesthetics: the theory of the novel (1998). The object and procedures of this study are characterized as explanatorybibliographical. The approachof the problem is qualitative, since this research identifies the emerging social voices of linguistic choices present in the short story Onde acaba o mapa, and analyzes the possible effects of meaning arising from these choices. This paper presents two theoretical chapters and one of analysis. The first theoretical chapter outlines the concept of sign for the Bakhtin Circle. The second chapter defines the concept of enunciation, according to concepts derived from Bakhtin's Circle theory, as theme, intonation, interaction and heteroglossia. The analysis chapter, as announced, identifies the emerging voices of the language choices present in the chosen short story and analyzes the possible effects of meaning arising from these choices. The work of analysis has showed us that the short story Onde acaba o mapa, da obra Sem vista para o mar (contos de fuga), which was written by Carol Rodrigues, brings the marks of the social and ideological environment stratified in the narrator's talk and the characters of the short story, through the theme and the intonation of signs.